2012
DOI: 10.1371/journal.pone.0052329
|View full text |Cite
|
Sign up to set email alerts
|

The h-Current in the Substantia Nigra pars Compacta Neurons: A Re-examination

Abstract: The properties of the hyperpolarization-activated cation current (Ih) were investigated in rat substantia nigra - pars compacta (SNc) principal neurons using patch-clamp recordings in thin slices. A reliable identification of single dopaminergic neurons was made possible by the use of a transgenic line of mice expressing eGFP under the tyrosine hydroxylase promoter. The effects of temperature and different protocols on the Ih kinetics showed that, at 37°C and minimizing the disturbance of the intracellular mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 109 publications
(133 reference statements)
5
9
0
Order By: Relevance
“…As observed in other systems [42], [49] the increase of intracellular levels of cAMP also changes the activation time course of the h-current onset: in experiments conducted in high [K + ] o saline (EC3), we observed adecreasing activation time constant both with forskolin (from 141.75±13.81 to 95.58±17.94, n = 7, P<0.02) and with 8Br-cAMP (from 130.27±26.16 to 103.21±23.48, n = 7, P<0.02).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As observed in other systems [42], [49] the increase of intracellular levels of cAMP also changes the activation time course of the h-current onset: in experiments conducted in high [K + ] o saline (EC3), we observed adecreasing activation time constant both with forskolin (from 141.75±13.81 to 95.58±17.94, n = 7, P<0.02) and with 8Br-cAMP (from 130.27±26.16 to 103.21±23.48, n = 7, P<0.02).…”
Section: Resultssupporting
confidence: 78%
“…1 was solved numerically for t using standard numerical methods [40], [41] solving Eqn. 1 for f(t)  = 90 and 10 (the Matlab code used can be found in the Supplementary material of [42]), thereby obtaining t 10 and t 90 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature did not further depolarize the activation range of I H . In the substantia nigra increasing recording temperature depolarizes the activation range of I H by as much as 15-20 mV (Gambardella et al, 2012). Here we found that recording in 500 M db-cAMP with an elevated temperature (35°C) did not further depolarize the activation range of I H (Fig.…”
Section: Modulating the Voltage-dependent Activation Range Of I Hsupporting
confidence: 48%
“…Third, we used 100 and 500 M db-cAMP, a non-hydrolysable version of cAMP that resists degradation by phosphodiesterases. Fourth, we tested if the activation of I H is further enhanced by increasing recording temperature, as previously reported in the substantia nigra (Gambardella et al, 2012).…”
Section: Enhancing the Activation Of I H By Controlling Camp Concentrmentioning
confidence: 90%
“…I h is an inward (depolarizing) Na ϩ /K ϩ current carried by hyperpolarization-activated cyclic nucleotide gated (HCN) channels. Consistent with evidence that cooling inhibits I h (11,37,40), we found cooling eliminated the depolarizing voltage "sag" caused by activation of I h during negative current injection (47). Inhibition of an excitatory membrane current associated with pacemaking is seemingly at odds with our findings that LC neurons intrinsically increase spontaneous discharge at cold temperatures.…”
supporting
confidence: 87%